Kontroversi Sejarah Kehadiran Islam di Bima - M Fachrir Rahman (Ulumuna, 2005)
Islam did not reach simultaneously many areas in Indonesia in same time, but in very various and large time span depend on location and access way that the areas respectively has. This is why islamization process in one area or island differed in time of beginning and taking from others. Bima, used to be a Hindu Kingdom in Sumbawa island, received Islamic proselytizing in the beginning of 17th century. It was preached by some Moslem traders functioning as proselytizers or might be the proselytizers in origin but pretended as traders. Islam coming to Bima was welcomed and directly embraced by the royal family of Bima Kingdom. It took so great benefit in Islamic preach that almost all people followed them, embracing Islam. All the historical evidences lead us to a conclusion that Islam come to Bima peacefully and spread structurally in terms of it was embraced by the king first and later, following him, by his family and almost all of his people. Islam embraced by Bimanese people less or more has the same type as it embraced by the Makassar people. Some socio-cultural descriptions are presented in this article to explain the connection between the two people especially in the context of islamization in Bima.